2017
DOI: 10.1177/0095327x17720922
|View full text |Cite
|
Sign up to set email alerts
|

Primary Unit Cohesion Among the Peshmerga and Hezbollah

Abstract: This study analyzes the creation of primary unit cohesion among the Kurdish Peshmerga soldiers fighting the Islamic State in northern Iraq and among Hezbollah fighters active in Syria. For this comparative study, Kurdish soldiers were interviewed on three fronts outside Mosul, Erbil, and Kirkuk in February 2015 and May 2016, and Hezbollah fighters were interviewed in Lebanon in March 2016. In contrast to many studies’ depictions of unit cohesion as relating to shared experiences of training and battle, this st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 22 publications
(16 reference statements)
1
5
0
Order By: Relevance
“…The same affirmation of existing research is evidenced in Nilsson’s (2018) piece on cohesion in the Pershmerga and Hezbollah. This article includes some fascinating interviews with Kurdish and Lebanese fighters.…”
supporting
confidence: 82%
“…The same affirmation of existing research is evidenced in Nilsson’s (2018) piece on cohesion in the Pershmerga and Hezbollah. This article includes some fascinating interviews with Kurdish and Lebanese fighters.…”
supporting
confidence: 82%
“…• A small number of studies found that groups with shared culture-such as shared attitudes, rituals, heritage, national pride, or religious identity-have higher cohesion (Boer and Abubakar, 2014;Christensen et al, 2006;Nilsson, 2018).…”
Section: Shared Culturementioning
confidence: 99%
“…Siebold (2007) indicated cohesion has horizontal, vertical, organizational, and institutional components and defined it as "a social-relationship product or form generated by the interaction and experiences of the group members in the context of their daily military activities, combat and noncombat" (p. 288). Nilsson (2018) broadly defined cohesion in a military unit as "the tendency of groups to stick together and involves interpersonal bonds, trust, and a sense of obligation to group members" (p. 648). However, this definition may be too narrowly focused on the unit level to compare it to what cohesion at a higher organizational level may entail.…”
Section: Examining the Similarities With Cohesionmentioning
confidence: 99%